HIDRÓXISSAIS LAMELARES DE COBALTO COMO MATERIAIS ADSORVENTES DO CORANTE AMARELO CREPÚSCULO - Teixeira, Danilo Augusto (2018)
This work had studied cobalt layered hydroxides salts synthesized by the urea method, undergoing a factorial optimization, in which the parameters used were the time and temperature of synthesis, from the salts: cobalt chloride, cobalt nitrate and cobalt sulfate. The layered hydroxide salts synthesized were used as adsorbents for the removal of Sunset Yellow dye, by the adsorption methods. This study was separated in two parts, the first adsorption part, was executed to evaluated the materials and choose one material that had a good response to the method. The chosen one was the cobalt hydroxychloride obtained at 110 °C and 3 hours of reaction, which presented better results of crystallinity, amount of adsorption (474.00 mg.g-1) and a yield of 73.7%. Thus, the cobalt hydroxychloride was utilized in a second adsorption study (second part), that consisted of the adsorption isotherms, analyzed by the Langmuir and Freundlich isotherm models. The best fitting isotherm was the Langmuir model and the thermodynamic adsorption parameters indicated that the process is exothermic due to its enthalpy value (ΔH ° = -18.53 kJ.mol-1) and spontaneous due to its Gibbs energy values (ΔG ° = -246.81; -743.10 and -2254.57 J.mol-1). The characterization of the adsorbents materials before and after the adsorption process was done by X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled with X-ray dispersive energy (EDS), Ultraviolet-visible spectroscopy (UV-VIS), infrared spectroscopy (FTIR) and thermogravimetry (TGA-DSC).